Projecto Obesidade Zero - Rito, Ana Isabel (2012)
Introduction: Childhood Obesity represents one of the most serious public health challenges, as it reached epidemic levels in several countries around the world. The prevention and treatment of this disease should be a top priority. The interventions used within childhood obesity approach should be community and family based and should essentially lie upon behaviour modification regarding diet and physical activity. The main purpose of the Project Obesity Zero (POZ) is to tackle childhood obesity at municipality level trough a set of activities (Healthy cooking programme and a nutritional guidance programme) targeted at low income families with overweight children. Methods: A Quasi-experimental multicentric study, developed in 2009 in five portuguese municipalities from the five regions of Portugal: Melgaço - North, Mealhada- Centre, Cascais - Great Lisbon, Beja – Alentejo and Silves- Algarve articulated with Healthcare centres and local governments. The program offered, to children and their families, a four stages intervention: a) 4 sessions of Individual Nutrition Counselling, b) a Healthy Cooking workshop, c) 2 children’s group sessions (nutrition and physical activity) and d) a Parents/families Group counselling. Outcomes of nutritional status were assessed at baseline and at 6 months after. Results: Of the 293 children participants in the intervention (47,5% boys and 52,9% girls; mean age 8,6 years; mean percentile 93,6), 220 (75%) have completed the program. Mean percentile decreased by 2,369 (P< 0,05). Conclusions: These data suggest that interventions at local level can have significant effects on childhood overweight prevalence. This knowledge may identify additional potential effective interventions in order to reverse the obesity trends in Portuguese children, one of the highest in Europe.